Designing a Digital Mentoring Model to Enhance Organizational Resilience in Energy Service Companies: A Pathway Toward Smart Process Transformation - Abousaeidi, Hossein; Fatehirad, Navid; Kamali, Mohammad Jalal (Management Strategies and Engineering Sciences, 2026)
This study aims to design and validate a digital mentoring model that enhances organizational resilience in energy service companies. A mixed-methods exploratory design was employed, integrating qualitative interviews and quantitative modeling. In the qualitative phase, semi-structured interviews were conducted with 15 experts in human resources, information technology, and organizational development, and the data were analyzed using thematic analysis in MAXQDA 2022. The quantitative phase utilized a researcher-developed questionnaire based on qualitative findings and was distributed to 130 randomly selected employees of the National Gas Company of Kerman Province. Measurement and structural models were assessed using PLS-SEM in SmartPLS 4, with reliability, convergent validity, and model-fit indices evaluated according to accepted thresholds. Inferential results showed that digital mentoring exerted a strong and significant direct effect on smart learning (β = 0.67, t = 12.84, p < 0.001). Smart learning significantly predicted organizational resilience (β = 0.59, t = 10.47, p < 0.001). An indirect mediation effect indicated that digital mentoring influenced organizational resilience through smart learning (β = 0.39, t = 3.98, p < 0.01). Digital transformational leadership demonstrated a significant moderating effect, strengthening the relationship between digital mentoring and resilience (β = 0.21, t = 2.06, p < 0.05). Model-fit indices supported the robustness of the structural model, including SRMR = 0.046, NFI = 0.91, and R² values of 0.45 for smart learning and 0.54 for resilience. Digital mentoring functions as a strategic learning and development mechanism that enhances resilience by improving adaptive learning capability, strengthening digital readiness, and enabling more effective leadership support. The validated model demonstrates that integrating digital mentoring into organizational development strategies can significantly reinforce resilience in technology-driven service environments.